Induction of Glutathione Synthesis and Glutathione Reductase Activity by Abiotic Stresses in Maize and Wheat - Gábor Kocsy; Gabriella Szalai; Gabor Gáliba (The Scientific World Journal)
The effect of different abiotic stresses (extreme temperatures and osmotic stress) on the synthesis of glutathione and hydroxymethylglutathione, on the ratio of the reduced to oxidised forms of these thiols (GSH/GSSG, hmGSH/hmGSSG), and on the glutathione reductase (GR) activity was studied in maize and wheat genotypes having different sensitivity to low temperature stress. Cold treatment induced a greater increase in total glutathione (TG) content and in GR activity in tolerant genotypes of both species than in sensitive ones. The GSH/GSSG and hmGSH/hmGSSG ratios were increased by this treatment only in the frost-tolerant wheat variety. High-temperature stress increased the TG content and the GSH/GSSG ratio only in the chilling-sensitive maize genotype, but GR activity was greater after this treatment in both maize genotypes. Osmotic stress resulted in a great increase in the TG content in wheat and the GR activity in maize. The amount of total hydroxymethylglutathione increased following all stress treatments. These results indicate the involvement of these antioxidants in the stress responses of wheat and maize.